Oleuropein Degradation Kinetics in Olive Leaf and Its Aqueous Extracts - María Esther Martínez-Navarro; Cristina Cebrián-Tarancón; José Oliva; María Rosario Salinas; Gonzalo L. Alonso (MDPI AG, 2021)
Although olives leaves are currently considered a waste material from oil mills, they have great potential to be transformed into by-products due to their high oleuropein content. Oleuropein is a glycoside precursor of hydroxytyrosol, which is the phenolic compound with the highest antioxidant capacity in nature and which is associated with multiple health benefits. For this reason, the demand for oleuropein is growing in the pharmaceutical, cosmetic and food sectors. The objective of this study is to determine the stability of oleuropein in olive leaves from oil mills in solid and aqueous forms under different conditions of temperature, relative humidity and lighting. The results indicate that the degradation of oleuropein conforms well to first-order kinetics. The rate constants at the temperatures tested in the aqueous extracts indicate activation energies from RTl to 80 °C and from 7 °C to 14 °C, as the degradation reactions were different in these ranges. Furthermore, olive leaf powder stored at any temperature with an RH ≥ 57% showed greater stability after six months, which is an encouraging result for the storage and transformation of this waste in oil mills.